Recovering the Liquidator's Costs on the Winding up of a Corporate Trustee - Stace, Victoria (Victoria University of Wellington Law Review, 2019)
High Court decisions in New Zealand have identified three possible legal bases that might allow a liquidator to pay its costs out of the trust assets, on the liquidation of an assetless company that acted as trustee of a trading trust. This article suggests that there are problems with each of the bases identified, and that legislative amendment is required to ensure that the liquidator's authority to have access to trust assets to pay for the costs of liquidation in these circumstances is clearly established.